180:oral Designing health benefit packages for universal health coverage – should countries follow a sectoral, incremental or hybrid approach?. (28th April 2022) - Baltussen, Rob; Surgey, Gavin; Vassall, Anna; Norheim, Ole F; Chalkidou, Kalipso; Siddiqi, Sameen; Nouhi, Mojtiba; Youngkong, Sitaporn; Jansen, Maarten; Bijlmakers, Leon; Oortwijn, Wija
Abstract : Countries around the world are increasingly rethinking the design of their health benefit package to achieve universal health coverage. Countries can periodically revise their packages by performing sectoral analyses, i.e. by evaluating a broad set of services against a 'doing nothing' scenario using a budget constraint. Alternatively, they can carry out incremental analyses, i.e. to evaluate specific services against current practice using a cost-effectiveness threshold. In addition, countries may employ hybrid approaches. This paper compares these approaches in terms of the nature of allocative inefficiencies, quality of analysis, political feasibility of reallocation decisions, and integrated health system analysis. Sectoral analysis is especially suited in contexts with large allocative inefficiencies in current service provision and can, in theory, realize large efficiency gains. However, it may be challenging to implement a comprehensive redesign of the package in practice. Incremental analysis is especially relevant in contexts where specific new services raise challenges to the allocative efficiency and sustainability of the health system. It may potentially support efficiency improvement, but its focus has typically been on new services while existing inefficiencies remain unchallenged. The use of hybrid approach may be a way forward to address the strengths and weaknesses of sectoral and incremental analysis.